2022
DOI: 10.3389/fnagi.2022.909303
|View full text |Cite
|
Sign up to set email alerts
|

The Double-Faceted Role of Leucine-Rich Repeat Kinase 2 in the Immunopathogenesis of Parkinson’s Disease

Abstract: Leucine-rich repeat kinase 2 (LRRK2) is one of the most common causative genes in Parkinson’s disease (PD). The complex structure of this multiple domains’ protein determines its versatile functions in multiple physiological processes, including migration, autophagy, phagocytosis, and mitochondrial function, among others. Mounting studies have also demonstrated the role of LRRK2 in mediating neuroinflammation, the prominent hallmark of PD, and intricate functions in immune cells, such as microglia, macrophages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 142 publications
(169 reference statements)
0
7
0
Order By: Relevance
“…Parkinson's disease-associated LRRK2 mutations enhance neuroinflammatory responses, increasing dopaminergic neuron loss and motor deficits. Experiments have shown that the knockdown of the LRRK2 gene in LRRK2 (R1441G) transgenic mice inhibits the conversion of microglia to a proinflammatory phenotype (Magistrelli et al, 2022;Zhang et al, 2022). Microglia-specific regulatory chromatin regions regulate LRRK2 expression in the human frontal cortex and substantiate these results in a human-induced pluripotent stem cell-derived microglia model (Langston et al, 2022).…”
Section: Microglia and Parkinson's Diseasementioning
confidence: 77%
“…Parkinson's disease-associated LRRK2 mutations enhance neuroinflammatory responses, increasing dopaminergic neuron loss and motor deficits. Experiments have shown that the knockdown of the LRRK2 gene in LRRK2 (R1441G) transgenic mice inhibits the conversion of microglia to a proinflammatory phenotype (Magistrelli et al, 2022;Zhang et al, 2022). Microglia-specific regulatory chromatin regions regulate LRRK2 expression in the human frontal cortex and substantiate these results in a human-induced pluripotent stem cell-derived microglia model (Langston et al, 2022).…”
Section: Microglia and Parkinson's Diseasementioning
confidence: 77%
“…In addition, the relationship between LRRK2, another important PD-related protein, and autophagy and neuroinflammation has been extensively studied. We can learn more about the relationship between LRRK2 and microglial autophagy from a recently published review ( Zhang et al, 2022 ).…”
Section: Microglia Recognize Pathogens By Pattern Recognition Receptorsmentioning
confidence: 99%
“…Large numbers of microglia expressing human leucocyte antigen (HLA)-DR have been detected in the brain of PD patients, particularly in areas of maximal neurodegeneration ( 15 , 17 ). Leucine-rich repeat kinase 2 ( LRRK2 ), a risk gene of PD, is highly expressed in microglia, monocytes and other immune cells ( 18 ), and has been reported to be associated with an increasing risk of Crohn’s disease, an inflammatory bowel disease and other autoimmune diseases ( 19 21 ). Alpha-synuclein specific T cell reactivity is associated with HLA-DRB1*15:01 and -DRB5*01:01 ( 22 , 23 ), and with preclinical and early PD ( 24 , 25 ), and the infiltration of CD4+ lymphocytes into the brain contributes to neurodegeneration in a mouse model of PD ( 15 , 26 ).…”
Section: Introductionmentioning
confidence: 99%